Deficiency of thiamine and Wernicke-Korsakoff syndrome – review of pathophysiology, clinical presentation , diagnostics and treatment - Zdunek, Roksana; Strus, Karolina; Madera, Magdalena; Dąbrowska, Natalia; Mazur, Sylwia; Mazur, Agata; Bizan, Aleksy; Nagórska, Emilia; Marcinkowski, Krzysztof; Kublińska, Aleksandra (Journal of Education, Health and Sport, 2024)
Introduction and aim of the study: Thiamine is a water-soluble vitamine, which bioactive form is necessary for energy metabolism in all cells. Deficiency of thiamine may be caused by malnutrition, alcoholism and certain diseases and it leads to an acute neuropsychiatric disorder called Wernicke encephalopathy. Untreated patients can develop a residual syndrome called Korsakoff syndrome. The aim of our study is to present current knowledge of history, pathophysiology, causes, symptoms and treatment of vitamine B1 depletion and Wernicke-Korsakoff’s syndrome. Material and methods: Our review is based on the analysis of materials collected in „Pubmed”, „Google Scholar” and other scientific articles using keywords: „thiamine”, „thiamine deficiency”, „Wernicke encephalopathy”, „Korsakoff syndrome”. Conclusions: Despite numerous studies, Wernicke encephalopathy is still difficult to diagnose. Attention should be paid to the possibility of vitamin B1 deficiency in people who are at risk of it like alcoholics, malnourished or psychiatric patients. Wernicke encephalopathy is an acute neuropsychiatric disorder so the treatment should be started as soon as possible to reduce the risk of developing Korsakoff syndrome.